Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1155/2009/803069
|View full text |Cite
|
Sign up to set email alerts
|

Computational Challenges in miRNA Target Predictions: To Be or Not to Be a True Target?

Abstract: All microRNA (miRNA) target—finder algorithms return lists of candidate target genes. How valid is that output in a biological setting? Transcriptome analysis has proven to be a useful approach to determine mRNA targets. Time course mRNA microarray experiments may reliably identify downregulated genes in response to overexpression of specific miRNA. The approach may miss some miRNA targets that are principally downregulated at the protein level. However, the high-throughput capacity of the assay makes it an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 48 publications
0
69
0
Order By: Relevance
“…Measuring target prediction performance has been recently addressed in few literature reviews. Most of these reviews compared target prediction approaches either from algorithmic point of view [1,13], or using the estimated false positive rates [12] or using small numbers of experimentally validated miRNA targets [21]. However, using only false positive or true positive rates is not sufficient to indicate the prediction performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring target prediction performance has been recently addressed in few literature reviews. Most of these reviews compared target prediction approaches either from algorithmic point of view [1,13], or using the estimated false positive rates [12] or using small numbers of experimentally validated miRNA targets [21]. However, using only false positive or true positive rates is not sufficient to indicate the prediction performance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…microRNAs (miRNAs) are a class of novel post-transcriptional gene expression regulators which are involved in a variety of developmental, physiological or disease-associated cellular processes [1]. They bind to their targets, messenger RNAs (mRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Often a single approach is not sufficient to give a comprehensive picture of hepatic dysfunctions occurring in NAFLD, and somewhat, a multiple-approach combination of different techniques is recommended. 12 Calvert et al 13 showed a good example of integration of system biology with reverse-phase protein microarray analysis to define genetic architecture of NAFLD. Very recently, also microRNA (miRNA) expression profiling has provided important insights into molecular mechanisms involved in the development of NAFLD.…”
mentioning
confidence: 99%
“…Various computational algorithms are currently used to predict the target genes of microRNAs. However, since a single microRNA can directly target Ͼ200 genes and each mRNA may be regulated by several microRNAs (6,40), computational challenges in microRNA-mediated regulation persist. As a result, there have been several approaches taken to analyze microRNA and gene expression data, such as performing cluster analysis or computing correlation coefficients for microRNA and mRNA target expression (34,37,50,68).…”
mentioning
confidence: 99%